Expertise-based randomized clinical trial of laparoscopic versus small-incision open cholecystectomy (Br J Surg 2013; 100: 886–894). Issue 3 (27th January 2014) - Naraynsingh, V; Singh, Y; Dan, D; Maharaj, R
Abstract: The Editors welcome topical correspondence from readers relating to articles published in the Journal. Responses should be sent electronically via the BJS website ( www.bjs.co.uk ). All letters will be reviewed and, if approved, appear on the website. A selection of these will be edited and published in the Journal. Letters must be no more than 250 words in length .